Long non-coding RNA NBR2 suppresses the progress of colorectal cancer in vitro and in vivo by regulating the polarization of TAM - Fuji Lai (Taylor & Francis Group, 2021)
Colorectal cancer (CRC) threatens the health of patients with high mortality, which lacks sensitive biomarkers for diagnosis to improve total survival. The lncRNA NBR2 is reported to be downregulated in CRC and suppresses the proliferation of CRC cells. However, the underlying mechanisms remain unclear. The present study aimed to explore the regulatory function of the lncRNA NBR2 on tumor-associated macrophage (TAM) polarization and its consequent anti-tumor effect. Two CRC cell lines were used in this study. We found that the lncRNA NBR2, TNF-α, and HLA-DR were downregulated, and Arg-1, CD163, CD206, and IL-4 were upregulated in CRC tumors. M1 polarization was activated and M2 polarization was suppressed in NBR2-overexpressed macrophages, accompanied by increased production of inflammatory factors, decreased proliferation, and inhibited migration ability in the co-culture system of HCT-116 cells (SW480 cells) and NBR2-overexpressed macrophages. The promoted proliferation and migration were observed in the co-culture system of HCT-116 cells (SW480 cells) and NBR2-knockdown macrophages. The tumor growth of both HCT-116 cells and SW480 cells in the xenograft model was suppressed by co-planting NBR2-overexpressed macrophages and was facilitated by the co-planting of NBR2-knockdown macrophages. The release of inflammatory factors was induced, M1 polarization was facilitated, and M2 polarization was suppressed in tumor tissues in the NBR2-overexpressed group, which were all reversed in the NBR2-knockdown group. Therefore, the lncRNA NBR2 suppressed the progression of colorectal cancer in vitro and in vivo by regulating TAM polarization.